EVALUASI DAMPAK BIDANG EKONOMI PROGRAM GERAKAN TERPADU BIDANG KESEHATAN EKONOMI PENDIDIKAN INFRASTRUKTUR DAN LINGKUNGAN (GERDU KEMPLING) KELURAHAN GEMAH KECAMATAN PEDURUNGAN TAHUN 2013 - Achmad Syaifudin Ansori; Dewi Rostyaningsih; Sundarso Sundarso; Sri Suwitri (Journal of Public Policy and Management Review, 2016)
Gemah village is one of many village which aimed by Gerdu Kempling program, but this village through the year showing the increase of poor people. The purpose of this study is to know about process of Gerdu Kempling in Gemah village, knowing output of Gerdu Kempling program, make a description about the impact of Gerdu Kempling program and supporting factor and resistor factor of Gerdu Kempling program in Gemah village. This research uses qualitative method research, using purposive technique and triangulation technique. The first process is to search poor people to include the list of getting aid, then they will do verification. Then the aid for receiver is based on the characteristic of the village and characteristic of inhabitant. The last process is monitoring and evaluation, which doing every three months and two years for monitoring and evaluation on the field. The output of this program is receiver got aid like skill coaching and work equipment.The result of the research shows that output from Gerdu Kempling program in Gemah village was not effective and not equal. Individual impact still not satisfied, but quite right on target and made people behavior to the positive side. Organization impact was not satisfied and not right on the target, did nothing in people behavior and show many demerits from implementer project. Societal impact shows that this program still can’t solve the problem, but good enough to make a change of a person’s behavior to the positive side. Institution and social system impact show that this program still can’t solve the poverty problem, there was no target to achieve and many demerits from implementer project. Recommendation for this program is to increase the actor from many sectors, increasing prices of aid, make budget standards, doing verification, monitoring and mentoring, do socialization in order to people more active, make safeguard networking and make a target.